Capture‐C reveals preformed chromatin interactions between HIF‐binding sites and distant promoters - Platt, J; Salama, R; Smythies, J; Choudhry, H; Davies, J; Hughes, J; Ratcliffe, P; Mole, D (EMBO Press, 2016)
Hypoxia‐inducible factor (HIF) directs an extensive transcriptional cascade that transduces numerous adaptive responses to hypoxia. Pan‐genomic analyses, using chromatin immunoprecipitation and transcript profiling, have revealed large numbers of HIF‐binding sites that are generally associated with hypoxia‐inducible transcripts, even over long chromosomal distances. However, these studies do not define the specific targets of HIF‐binding sites and do not reveal how induction of HIF affects chromatin conformation over distantly connected functional elements. To address these questions, we deployed a recently developed chromosome conformation assay that enables simultaneous high‐resolution analyses from multiple viewpoints. These assays defined specific long‐range interactions between intergenic HIF‐binding regions and one or more promoters of hypoxia‐inducible genes, revealing the existence of multiple enhancer–promoter, promoter–enhancer, and enhancer–enhancer interactions. However, neither short‐term activation of HIF by hypoxia, nor long‐term stabilization of HIF in von Hippel–Lindau (VHL)‐defective cells greatly alters these interactions, indicating that at least under these conditions, HIF can operate on preexisting patterns of chromatin–chromatin interactions that define potential transcriptional targets and permit rapid gene activation by hypoxic stress.